SOCIAL CHANGE AND CRITICISM OF MODERN LIFE IN NECATI MERT'S STORIES - GEDİKLİ , Özgür (SSD Journal, 2021)
The changes seen in the social structure and in the family, religion, morality, economic etc. elements that make up it are called social change. There are transitions to different situations or differentiation in institutions with the changes that occur in every society, can be seen in a partial area of life or in all of them. Changes is faster in material structures while faces resistance in religion, family etc. and change brings changes. Changes causes social depressions ıf it happens quickly and with insufficient infrastructure. Westernization has continued in the Republic began in the Ottoman Empire in Turkey, has caused traumatic, radical social changes and transformations with the modern life. Thus a conflicted, distorted and contradictory life has emerged in economy, urbanization, family, religion etc. These changes and their problems have been handled by many artists. Necati Mert also told the Turkey experienced the change that which took place in the history of the last forty years in his stories. He has dealt with the break from the past, the destruction of local characteristics, social dissolution, individuality and loneliness brought about by urbanization, vanishing values and traditions, degenerate human relations, degeneration, religion and human tragedy in modernizing-globalizingsecularizing daily life in his stories. He enabled the reader to witness the transformations in society and sometimes he analyzed social events. In this study, the author's approach to social changes in his stories and his critique of modern life will be evaluated within the framework of the understanding of economy-livelihood, technologyscience, family, woman and child, urbanization, religion and morality.